Questioning assumptions….and practices! - Editorial Team of Babylonia (Babylonia, 2023)
In a "society of opinion" such as ours, where scientific arguments are discredited in favor of Internet-educated "critical thinkers", the role of postulations and beliefs influencing our worldviews needs some discussion. Perhaps more fundamentall, we researchers and educationalists should be questioning our practices, our ethics, and our way of sharing empirically acquired knowledge.